Acute Toxicity Test of The Jamu TurmericTamarind on Artemia Salina Leach Larvae - Muhammad Abdurrahman Fardiaz; Kholisatun Nafila Az-Zahro; Intan Dzulqaidah; Diana Ayu Savitri; Iman Surya Pratama; Lalu Husnul Hidayat (Jurnal Biologi Tropis, 2023)
Jamu is an ingredient from plant, animal material, mineral material, or a mixture of these ingredients for treatment based on experience. One of the jamu that are often consumed by Indonesian people, especially women, is the turmeric tamarind jamu. The turmeric and tamarind jamu is believed by most women to relieve pain during menstruation period. However, its current use has not been accompanied by the optimum dosage and side effects. Therefore, the toxicity test was carried out as an initial screening to predict the toxic levels that might be caused by the turmeric tamarind jamu. In this study, the bioactive substances in turmeric tamarind jamu will be identified, as well as the level of toxicity based on the LC50 value. Using variations in extract concentration, this study used a fully randomized approach. The powdered sample of turmeric tamarind jamu brand X was dissolved in water and then tested for phytochemical screening. Phytochemical screening including flavonoids, alkaloids, tannins, steroids/terpenoids, and saponins screening was carried out qualitatively, the Brine Shrimp Lethality Test (BSLT) method was used to carry out the toxicity.The results of the phytochemical screening showed that the turmeric tamarind jamu contains alkaloids, flavonoids, tepenoid, steroid and tannins. The results of the toxicity test of the turmeric tamarind jamu showed the LC50 value in 3366.656 ppm and classified as non-toxic because it had LC50 value more than 1000 ppm.